-7+2x+x=11

Simple and best practice solution for -7+2x+x=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7+2x+x=11 equation:


Simplifying
-7 + 2x + x = 11

Combine like terms: 2x + x = 3x
-7 + 3x = 11

Solving
-7 + 3x = 11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + 3x = 11 + 7

Combine like terms: -7 + 7 = 0
0 + 3x = 11 + 7
3x = 11 + 7

Combine like terms: 11 + 7 = 18
3x = 18

Divide each side by '3'.
x = 6

Simplifying
x = 6

See similar equations:

| (n+6)=7n+42 | | =849-2(18.4282) | | 15-3x+4=3 | | r^2-35+75=0 | | 3x-5+4x+1=n | | 8=4x-7x+6 | | X+3Y-2Z=11 | | 4x+7-x-14= | | m^2+6m+4=0 | | ln(x+2)+ln(x)=ln(12+x) | | 3-5x+8=-2 | | 2x^2-18x=-2x^2-7x-6 | | 11-4y=-9 | | y+5=2y-3 | | 3+3x=x+13 | | 2(2d+5)=3(8-d) | | n^2-18n+81=40 | | X-2+4x=38 | | Cx+hy= | | (A-9)(2a-1)=0 | | 25600p=(p+12)(-p+20) | | -3b+-b= | | bx+hy=kforx | | 9p+2=4p-11 | | c=1/2mr | | -10x+50=400 | | 42/b=14 | | 27+3y-11=15y-12-5y | | -4.9x-6=-4.1x+2 | | 3(-2)-y=2 | | 100+10= | | 5n-2=-32 |

Equations solver categories